Magnolia ottoi (Magnoliaceae) a new species from Purulhá, Baja Verapaz, Guatemala: conservation and Mayan Q’eqchi ‘ ethnotaxonomy - Vázquez García, J. Antonio; Tribouillier Navas, Erick; Archila, Fredy; Véliz Pérez, Mario Esteban (Phytotaxa, 2020)
A new species of Magnolia subsect. Talauma (“jomcoj”), Magnolia ottoi, is described and illustrated. The conservation status of this new species is proposed as critically endangered (CR) according to IUCN criteria. An identification key and a map with the distribution of the new species and other species of Magnolia subsect. Talauma from Guatemala and neighboring areas (Honduras and Chiapas, México) is also presented. Our field research also unveiled the Mayan Q’eqchi’ ancestral taxonomic knowledge which differentiates magnolias of two different subsections, Magnolia and Talauma, based on wood quality and properties. They consistently distinguished them as “coj” and “jomcoj” respectively.